Augustine and Autobiography: Confessions as a Roadmap for Self-Reflection - Scott, Mark S. M. (Religions, 2015)
In this article, I explore a pedagogical strategy for teaching Augustine's Confessions to undergraduate students, which involves a final essay assignment. In the assignment, students compose their own confessions at the end of the term that employs Augustine's Confessions as a roadmap for rigorous self-reflection. Like Augustine, they must employ a creative literary frame, without duplicating his rhetorical technique of framing his autobiography as a prayer to God. Moreover, they must reflect on the salient questions, key people, pivotal moments that have shaped them, and analyze their shifts in worldviews. The assignment aims to demystify Augustine and to reinforce the evolving nature of the self as it moves through time and absorbs new ideas and experiences, as well as helping students begin to formulate a coherent and constructive life narrative.